Association between Life Stressors and Arterial Stiffness: The Finnish Retirement and Aging Study - Karelius Saana; Vahtera Jussi; Heinonen Olli J.; Niiranen Teemu J.; Stenholm Sari (BMC, 2022)
Objective: Besides traditional risk factors, other factors such as life stressors are linked with incident cardiovascular disease. However, the underlying mechanisms for this association remain mostly unknown. We studied the relation of life stressors (job strain, sleep loss due to worry, illness or death in family, financial difficulties and caregiving) and their accumulation with arterial stiffness, an independent predictor of cardiovascular disease.
Methods: 258 participants (mean age 62.4 years, 82% women) from the Finnish Retirement and Aging Study underwent measurements for carotid-femoral Pulse Wave Velocity (PWV), a standard criterion for assessing arterial stiffness and responded to a survey inquiring life stressors. Using analysis of covariance, we estimated group means adjusted for age, gender, occupation, lifestyle factors and hypertension.
Results: Participants with recent illness or death in family (8.04 m/s; 95% CI, 7.40-8.73 vs. 7.52 m/s; 95% CI, 7.03-8.05) and financial difficulties (8.65 m/s; 95% CI, 7.62-9.81 vs. 7.71 m/s; 95% CI, 7.21-8.24) had increased PWV compared to those who did not have exposed to these stressors independent of lifestyle factors, diabetes and systolic blood pressure. In addition, increasing number of life stressors demonstrated an association towards increased PWV (>= 2 stressors: 8.04 m/s; 95% CI, 7.42-8.72 vs. 0 stressors 7.74 m/s; 95% CI, 7.23-8.28; p for trend 0.27) but the association attenuated after adjusting for lifestyle factors, diabetes and systolic blood pressure.
Conclusion: Life stress was found to associate with higher arterial stiffness. Increased arterial stiffness could explain some of the increased cardiovascular disease risk related to life stressors.
HIGHLIGHTS
-Arterial stiffness was assesed as carotid-femoral pulse wave velocity.center dot
-Illness or death in the family were associated with an increased arterial stiffness.
-Financial difficulties were associated with an increased arterial stiffness.
-A trend toward increasing number of stressors and higher arterial stiffness exists.
(C) 2021 The Authors. Publishing services by Atlantis Press International B.V.